Melangkah ke dalam Kegelapan: Kajian Yuridis Tindak Pidana Pembunuhan dalam Pengaruh Alkohol - Emil Fitra Nur; Muhammad Natsir; Phireri Phireri; Khaerul Mannan (Jurnal Litigasi Amsir, 2024)
This research aims to analyze the considerations made by the panel of judges in delivering a decision on a murder case influenced by alcohol, as seen in Decision Number 62/Pid.B/2022/PN.Bar. Additionally, it investigates the application of the law by the panel of judges in reaching a verdict concerning this crime. This research adopts a normative approach, utilizing both statutory analysis and a case study. The findings reveal that the judge's decision-making process in the aforementioned case, Decision Number 62/Pid.B/2022/PN.Bar, was based on juridical considerations, including the evidence presented during the trial, as well as non-juridical factors, such as aggravating and mitigating circumstances related to the defendant. The application of the law by the panel of judges in delivering a verdict on the crime of murder influenced by alcohol in Decision Number 62/Pid.B/2022/PN.Bar was deemed appropriate and in accordance with the primary indictment put forth by the public prosecutor. The defendant's actions were considered both lawful and convincing, leading to a sentence of 7 (seven) years of imprisonment.